STUDI TENTANG BENTUK, MOTIF, WARNA DAN TEKNIK ANYAMAN TARATAK KENAGARIAN KUBANG DI KABUPATEN LIMA PULUH KOTA - Dra. Ernis, M.Pd., RAHMA YUNITA.A, Dra. Jupriani, M.Sn., (Serupa The Journal of Art Education, 2018)
This research was conducted in Jorong Taratak Kenagarian Kubang Kabupaten Lima Puluh Kota. Aiming to get information form, motif, color, and technique of webbing. This type of research is descriptive qualitative research. DataÂ  collection in this research is primary data that is Taratak webbing whileÂ  secondary data from books and internet. Conclusion of research: the source of ideas in woven mostly from geometric shapes. The types of woven forms are kombuik bulek, kombuik petak, kombuik cibia, combination bag, wallet, tissue box, table mat, mat daro pad bed mat, and pencil case. The names of the motifs are langkah satu / box, langkah duo, langkah tigo, kalaia sabolik, kalia silombok, kalaia rantai,kacang goreng, mato ikan, and capuak manggi. Types of colors used are red, pink, green, yellow, black, orange, and brown. And the technique used begins by creating a skeleton, one intermittent, and intermittent.Keywords: shape, motif, color, technique of webbing Taratak